Pengaruh Sustainable Marketing Terhadap Keputusan Pembelian Beras Organik - Purwanti, Ni Made Dwining; Satriawan, I Ketut; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): DesemberDO - 10.24843/JRMA.2021.v09.i04.p11, 2021)
Sustainable marketing as a marketing strategy concept can influence consumers to make purchasing decisions. The purpose of this study was to analyze the influence of sustainable marketing variables on the decision to purchase organic rice of S omya Pertiwi Agricultural and Rural Training Center (P4S) and to find out the right recommendations to be given to companies in the application of sustainable marketing. Sampling is done by sampling nonprobability sampling methods and data collection is done by distributing questionnaires and directly to respondents. Data analysis is done by structural equation modeling (SEM) method. The results obtained in this study are that purchasing decisions are influenced by customer solutions (X1) with direct influence of 35.5%, customer cost (X2) with direct influence of 25.7%, convenience (X3) with direct influence of 16.2%, communication (X4) with direct influence of 19.2%, and correlation (X4) with direct influence of 17.2%. Among the five variables, the customer solution is the variable that most influences purchasing decisions in P4S Somya Pertiwi with a value of 0.355, and the variable with the lowest effect is convenience with a value of 0.162. Keywords:  Sustainable marketing, purchasing decision, structural equation modeling (SEM)